Hubungan Antara Dukungan Sosial Terhadap Kecemasan Akademik pada Mahasiswa Yang menyusun Skripsi Di Masa Pandemi Covid-19 semester Genap Tahun Ajaran 2019/2020 - Winda Lestari; Dyah Astorini Wulandari (PSIMPHONI, 2021)
ABSTRACTThis study aims to determine the correlation between social support and academic anxiety in students compiling their thesis during the COVID-19 Pandemic Period in Even Semester Academic Year 2019/2020. Probability sampling with simple random sampling was used as the sampling technique in this study. The research subjects were 100 students. This research is a quantitative study with a validity test of the product-moment correlation technique. Academic Anxiety scale test shows a moving validity from 0.233 to 0.534 with 43 valid items with a reliability of 0.886. On the Social Support scale, it has a moving validity from 0.211 to 0.554 with 45 valid items. Based on the results of the Product Moment correlation hypothesis test, it shows a correlation value of -0.600 with p of 0.000 (p0.01) on the scale of social support and academic anxiety scale. It can be concluded that the hypothesis stating there is acorrelation between social support and academic anxiety is accepted. Keywords: Academic Anxiety; Social Support, Final-year Student